Topical Formulations of Binahong (Anredera cordifolia): Advances in Stability and Biological Efficacy - Alwi, Nur Azminah; Hendrayana, Made Agus; Wiryanthini, Ida Ayu Dewi (Riviera Publishing, 2026)
Topical formulations derived from Anredera cordifolia (Binahong) have gained increasing attention in dermatology and wound care due to their promising therapeutic properties. Despite growing experimental evidence, a systematic evaluation of formulation strategies, stability profiles, and biological efficacy remains limited. This review aims to comprehensively analyze recent advances in Binahong?based topical formulations, including gels, creams, nanoemulgels, and ointments, focusing on their phytochemical composition, physicochemical stability, skin penetration potential, and dermatological performance. Using structured literature review methodology, relevant studies published between 2015 and 2025 were identified from databases such as PubMed, Scopus, ScienceDirect, and Google Scholar. Data regarding formulation design, stability parameters, in vitro and in vivo efficacy, and research gaps were extracted and synthesized thematically. The findings indicate that Binahong formulations exhibit significant wound healing, anti?inflammatory, antimicrobial, and skin?rejuvenating effects, largely attributed to bioactive flavonoids, saponins, and tannins. However, critical limitations persist, including the lack of quantitative phytochemical standardization, insufficient long?term stability data, and minimal direct evidence on skin penetration. This review concludes that while Binahong holds considerable potential as a topical agent, future research must prioritize standardized extraction, rigorous stability testing, and mechanistic studies to support its translation into reliable, clinically effective dermatological products.